An Investigation of Risks Factors affect to Housing Loan’s Processes in Thailand Commercial Banks - Khumpaisal, Sukulpat; Meechai, Wiparut; Bunnag, Katkate (Archives of Business Research, 2017)
This paper presents an investigation of the risk factors that affect to the housing loan’s approval processes in Thailand’s 5 largest commercial banks, with the largest amount of housing loan’ Non Performing Loan (NPL). The data, obtained from 15 selected interviewees from 5 largest Thailand commercial banks, has been summarised, reported, and analysed by the qualitative content analysis technique. The interviewees include Mortgage Sales (Housing loan), Retail Credit Analyst and Credit Risk Analyst. The instruments, derived from both qualitative and quantitative approaches, to assess the borrowers’ credit risk were also formulated in this paper. The results from this study can be used as a benchmark for other Thai financial institutions in order to improve the housing loan’s approval processes.